GAMBARAN KEMAMPUAN BERPIKIR MATEMATIS, AKHLAK, DAN PRESTASI BELAJAR MATEMATIKA SISWA SMP DALAM PEMBELAJARAN BERBASIS BUDAYA ISLAM - Jazuli, Akhmad (2012)
The purpose of this research is (1) to describe the ability of mathematical thinking; (2) to describe contribution of Islamic culture values to the ability of mathematical thinking; and (3) to know correlation between akhlak and mathematics learning achievement of SMP students in Islamic Culture-Based Learning. This research is qualitative-quantitative research using mixed methods with sequential exploratory design. The subject is the 8th grade students in SMP Al Irsyad Al Islamiyyah Purwokerto, and six students who were selected as respondent. The results research is (1) the students' ability of mathematical thinking in the high learning achievement category is complete and very good, the students in the middle learning achievement category is fair good, deductive reasoning is dominant and creative thinking consist of fluency, originality, and elaboration. The students' ability of mathematical thinking in the low learning achievement category is poor, inductive reasoning is dominant and creative thinking only consist of originality component; (2) the implementation of Islamic culture value gives a positive contribution to akhlak (character) building and effectiveness of thinking ability. Tahfizh (recitation) of Al Qur'an enhances students' mathematical higher order thinking ability. The implementation of pray gives students' self confidence and discipline in solving mathematical problem; (3) There is strong correlationbetween akhlak and mathematics learning achievement.